2014
DOI: 10.1128/aem.00740-14
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Matrix-Assisted Laser Desorption Ionization (MALDI) Biotyping Workflow: in Search of Microorganism-Specific Tryptic Peptides Enabling Discrimination of Subspecies

Abstract: A well-accepted method for identification of microorganisms uses matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) coupled to analysis software which identifies and classifies the organism according to its ribosomal protein spectral profile. The method, called MALDI biotyping, is widely used in clinical diagnostics and has partly replaced conventional microbiological techniques such as biochemical identification due to its shorter time to result (minutes for MALDI biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…As previously stated, several reasons could explain the difficulty in distinguishing between the different enterococcal species present in this study. The workflow of the classical MALDI biotyping to discriminate at the species level revealed that about 10 times more proteins were detected compared to a classical MALDI-TOF MS protocol [40], like the one used in this work. Furthermore, although some improvements have been made in bacterial identification, a broadly applicable and useful sample preparation method prior to MALDI analysis is needed [31].…”
Section: Discussionmentioning
confidence: 97%
“…As previously stated, several reasons could explain the difficulty in distinguishing between the different enterococcal species present in this study. The workflow of the classical MALDI biotyping to discriminate at the species level revealed that about 10 times more proteins were detected compared to a classical MALDI-TOF MS protocol [40], like the one used in this work. Furthermore, although some improvements have been made in bacterial identification, a broadly applicable and useful sample preparation method prior to MALDI analysis is needed [31].…”
Section: Discussionmentioning
confidence: 97%
“…Extracts were analyzed in triplicate in both assays. Spectra with maximal absolute peak intensities ranging from 10 3 to 10 4 arbitrary units were considered for evaluation [42, 43]. …”
Section: Methodsmentioning
confidence: 99%
“…As for the highly sensitive species identification, discussed above, sample processing (e.g., tryptic digestion, acidic/organic extraction, nano-liquid chromatography) can greatly increase the sensitivity and specificity of a MALDI-TOF MS method and thus enable subspecies identification [66,75]. A further possibility is the functional modification of the MALDI target plates themselves, which was for example performed with antibodies for direct immunoaffinity MALDI-TOF MS of haptoglobin or by dioxide coating in order to enrich phosphopeptides [76,77].…”
Section: Sample Processing Can Broaden the Use Of Maldi Biotypingmentioning
confidence: 99%